Analisis Human Error pada Proses Pembuatan Baja di PT.RAVANA JAYA Menggunakan Metode Sherpa dan Heart - Denindra Surya Maulana; Hidayat Hidayat; Efta Dhartikasari Priyana (G-Tech: Jurnal Teknologi Terapan, 2025)
PT Ravana Jaya is a general contractor that works on steel fabrication and has several partners from small, medium, and large scale companies.  Observations show that errors often occur during the production process, leading to a number of defective products with a defect percentage of 0.12%. The allowable defect percentage ranges between 0.05% and 0.07%, or approximately 1-2 items per month.  Therefore, research should be conducted to look at the human errors that cause defective products during the production process.  This study utilized the Human Error Assessment and Reduction Technique (HEART) and Systematic Error Reduction and Prediction (SHERPA) methods.  According to this study, the highest predicted human error occurred in the welding task with a HEP value of 10.565, and the lowest human error occurred in the welding task with a HEP value of 10.565. To reduce the number of defective products, it is recommended to make improvements, such as conducting strict and regular evaluation and supervision, continuous training, adding dividers between parts, and changes in design.